Kontribusi Fasilitas, Motivasi Dan Konsidi Lingkungan Terhadap Kedisiplinan Belajar Peserta Didik Kelas XII SMK N 2 Purwodadi Tahun 2015/2016 - Yuhana, Ujuk, Prof. Dr. Sutama, M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
The objectives of this research are to analyze: the contribution of facilities of motivation and environment condition learning toward the students' learning discipline of the twelve grade students of SMK N 2 Purwodadi. The kind of this research is quantitative eresearch. The research was conducted at taken 194 respondents as the research sample with random sampling technique. Techniques of data collection used questionnaires. Technique of analyzing data used multiple linear regression analysis, accuracy test model, accuracy testestimation parameter, donations predictor and classical assumption. The results of this study state that : 1) The condition of facilities, motivation and the environment simultan eously have contributed to student discipline SMK N 2 Purwodadi with α 5% is 1,653 significant level 0.000< 0.05 and the effective contribution of 79.9 %. 2) facilities showed a significant effect on learning with significant level 0.000< 0.05 and the effective contribution of 30,43%.3 ) motivation showed significant impact on student learning discipline with significant level 0.000< 0.05 and the effective contribution of 21,38 %. 4) environmental conditions showed a significant effect on student learning discipline with significant level 0.000< 0.05 and the effective contribution of 28,09 %. So the facilities , motivation and environmental conditions simultaneously significant and positive impact on the discipline of learning